DO THE GOVERNMENT EXPENDITURE AUDITS CORRELATES WITH CORRUPTION IN THE PUBLIC PROCUREMENT? - Yanto, Deri; Adrison, Vid (Badan Pemeriksa Keuangan Republik Indonesia, 2020)
Public procurement is the main area of corruption in the government. This study aims to examine the correlation between government expenditure audit conducted by BPK and local government corruption behavior. This study uses a fixed effect panel regression approach and the dependent variable is the value of irregularities in the public procurement sector in all local governments in Indonesia. This study found that the government expenditure audit carried out in the previous period correlated with changes in local government corruption behavior. Local governments will reduce corruption behavior as an implication of changing views and calculating expected cost corruption based on their experience of being audited. Besides, local governments expect their probabilities to be re-audited. It is evident in the local government which has not been audited for three years that it will try to reduce its corrupt behavior because it is expected that this year will be audited again. This study suggests an increase in audit frequency that is expected to decrease the aggregate corruption level in public procurement in local government.